(JUGO)NOSTALGIJA KROZ NAOČALE POPULARNE KULTURE (Filološke studije, 2019)
The article analyses the concept of so called Yugonostalgia (the nostalgia for Yugoslav everyday life) in popular culture in former Yugoslav republics. It focuses on the popular song about Josip Broz Tito (Everything is the same, but he is gone) by famous Serbian singer Tijana Dapčević. After short notes about the idea of nostalgia and the „birth“ of the term, the author analyses how Yugonostalgia can be treated in popular music and popular cultures especially from the intercultural aspect.